2022
DOI: 10.1080/21645515.2021.2018894
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers and risk factors for the early prediction of immune-related adverse events: a review

Abstract: In recent years, immunotherapy has been widely used to treat patients with malignant tumors. While immune checkpoint inhibitors (ICIs) significantly improve the prognosis of cancer patients, the incidence of immune-related adverse events (irAEs) is increasing. Not only can irAEs accumulate in multiple organ systems throughout the body, but rare adverse reactions may also occur continuously. In severe cases, irAEs can be life-threatening or even lead to death. Therefore, the early identification, diagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 96 publications
0
16
0
1
Order By: Relevance
“…There is an urgent need to provide treatment options that produce better outcomes [19,20] . The role of immunotherapy in the treatment of EC is increasing as research into the mechanisms of tumor immunity continues to progress [21,22] . Molecular markers for immunotherapy fall into two categories, one associated with tumor neoplastic antigens; the other with the tumor in ammatory microenvironment [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an urgent need to provide treatment options that produce better outcomes [19,20] . The role of immunotherapy in the treatment of EC is increasing as research into the mechanisms of tumor immunity continues to progress [21,22] . Molecular markers for immunotherapy fall into two categories, one associated with tumor neoplastic antigens; the other with the tumor in ammatory microenvironment [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The immune cell in ltration score of CXCL9 was assessed in 9555 tumor samples from 39 tumor types using the CIBERSORT algorithm(Figure 9A). The expression data of CXCL9 and 150 marker genes of the ve immune pathways (chemokine (41), receptor (18), MHC (21), Immunoinhibitor (24), Immunostimulator (46)) were further extracted in each sample, and the pearson correlation between CXCL9 and the marker genes of the ve immune pathways was calculated(Figure 9B);In addition, the expression data of CXCL9 and 60 marker genes of two types of immune checkpoint pathways (Inhibitory (24), Stimulatory (36)) were extracted in each sample, and the pearson correlation between CXCL9 and immune checkpoint marker genes was calculated(Figure 9C). We also assessed the correlation between CXCL9 expression and 22 immune cells in endometrial cancer tissues by the CIBERSORT algorithm, showing that CD8 T cells, CD4 T cells, CD4 memory T cells, T cell follicular helper cells, NK cells, M1 macrophages, and dendritic cells had signi cantly higher immune function in the high expression group (Figure 9D).…”
Section: Immunoassaymentioning
confidence: 99%
“…For example, melanoma patients responded better to anti-PD-1 therapy when their tumor cells were rich in mutations in BRCA2, a gene important for homologous recombination in DNA repair ( 293 ). Mutation of B2M was also reported to be associated with initial resistance to anti PD-1 therapy in melanoma patients ( 294 , 295 ) ( 4 ). Potential biomarkers may predict the response to ICIs.…”
Section: Potential Biomarkers Of Ici Responsementioning
confidence: 99%
“…Firstly, immunotherapy exclusively targets immune cells and tumor cells, thus leaving other cells unscathed. Secondly, the adverse effects of immunotherapy are comparatively less severe than traditional chemotherapy and radiotherapy-treatment regimens ( 4 ). However, tumor cells are highly adaptable and can become unresponsive to immunotherapies, and therefore they continuously evolve mechanisms that evade host immunity and promote tumor persistence.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported increased risk of ICI induced cardiac irAEs in patients with elevated pre-treatment troponin. Mahmood and colleagues compared the data of patients with and without myocarditis after ICI treatment and found a four-fold increase in the risk of cardiac irAEs for patients with troponin T (cTnT) ≥ 1.5 ng/ml (116,121,128). Another retrospective cohort study demonstrated a seven fold risk of cardiac IrAEs in patient receiving ICIs with baseline troponin >0.01 ng/ml (HR: 7.27; 95% CI: 2.72 to 19.43; p < 0.001) (129).…”
Section: Cardiac Specific Biomarkersmentioning
confidence: 99%